Предмет: Математика,
автор: 9807069491
8(- y -2) = -5 y -(6 – 9 y)
Срочно
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
8(- y -2) = -5 y -(6 – 9 y)
-8y - 16 = -5y - 6 + 9y
-8y - 16 = 4y - 6
4y + 8y = -16 + 6
12y = -10
y = -10:12
y = -5/6
Автор ответа:
0
Ответ:
8(- y -2) = -5 y -(6 – 9 y)
-8y-16 = -5y-6+9y
-12y-10=0
-12y=10
12y=-10
Похожие вопросы
Предмет: Українська література,
автор: yberman
Предмет: Английский язык,
автор: o594tr
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: demidenkoleoxap6km7m
Предмет: Русский язык,
автор: vladamalaxova